Legal Reform of Term Limitations for Legislative Members as a Form of Institutional Reform - Sugiarto Sugiarto; Faisal Santiago (Cognitionis Civitatis et Politicae, 2024)
The limitation of the term of office for legislative members in Indonesia is an essential aspect of institutional reform aimed at improving democratic quality. This reform seeks to prevent the abuse of power and promote political regeneration.The research aims to analyze the implementation of term limits for legislative members, focusing on creating a more responsive, transparent, and accountable legislative system aligned with the aspirations of the people. This study employs a normative legal research method by analyzing constitutional provisions, election laws, and comparative practices in other democracies. Data collection involves literature reviews and legal documentation analysis. The research highlights key steps necessary for implementing term limits, such as amending the 1945 Constitution, revising election laws, and formulating detailed implementing regulations. Identified obstacles include resistance from incumbent legislators, political disagreements among parties, and challenges in law enforcement and oversight. Enforcing term limits for legislative members requires comprehensive legal reforms to ensure democratic quality and sustainable political renewal, despite significant political and institutional challenges.